Religiosity and Healthy Lifestyle Behaviours in Malaysian Muslims: The Mediating Role of Subjective Well-Being and Self-Regulation - Tey, Swan Ee (Journal of religion and health, 2018)
Past research on healthy lifestyle behaviours has been primarily conducted within Western or Judeo-Christian contexts, while non-Western or Muslim contexts remain under-represented. This study examined predictors of healthy lifestyle behaviours (religiosity, goal-setting, impulse control, and subjective well-being) in Malaysian Muslims and explored the mechanisms underlying the relationship between religiosity and healthy lifestyle behaviours. Self-report survey responses from 183 healthy adults (M age = 28.63 years, 18-50 years) were analysed using regression and multiple mediation analyses. The results indicated that subjective well-being emerged as the strongest predictor, followed by goal-setting. Furthermore, subjective well-being and goal-setting mediated the religiosity-healthy lifestyle behaviour relationship. The findings provide guidance for future health-promoting interventions.